Drawing Lines and Crossing Borders: Transformation Theory and Richard Rorty's Philosophy. (July 2019) - Eschenbacher, Saskia
This article aims at expanding transformation theory through the work of the philosopher Richard Rorty. His concept of redescription allows us to distinguish between good learning and transformative learning and to counteract the critique of conceptional looseness. In addition, Rorty's thesis of contingency and his notion of irony are going to be explored in respect to their implications for transformative learning theory.